Development and validation of the Reward Deficiency Syndrome Questionnaire (RDSQ-29). (March 2022) - Kótyuk, Eszter; Urbán, Róbert; Hende, Borbála; Richman, Mara; Magi, Anna; Király, Orsolya; Barta, Csaba; Griffiths, Mark D; Potenza, Marc N; Badgaiyan, Rajendra D; Blum, Kenneth; Demetrovics, Zsolt
Background: The reward deficiency syndrome (RDS) integrates psychological, neurological, and genetic factors of addictive, impulsive, and compulsive behaviors. However, to date, no instrument has been validated to assess the RDS construct. Aims: The present study developed and tested a tool to assess RDS. Methods: Data were collected on two college and university samples. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed on Sample 1 ( N = 1726), and confirmatory analysis was conducted on an independent sample ( N = 253). Impulsivity and sensation-seeking were assessed. Results: Based on EFAs, a 29-item Reward Deficiency Syndrome Questionnaire (RDSQ-29) was developed, containing four subscales (lack of sexual satisfaction, activity, social concerns, and risk-seeking behavior). CFA indicated good fit (comparative fit index (CFI) = 0.941; Tucker–Lewis index (TLI) = 0.933; root mean square error of approximation (RMSEA) = 0.068). Construct validity analysis showed strong relationship between sensation-seeking and the RDS scale. Conclusion: The RDSQ-29 is an adequate scale assessing psychological and behavioral aspects of RDS. The RDSQ-29 assesses psychological and behavioral characteristics that may contribute to addictions generally.